2019
DOI: 10.3389/fphys.2019.00907
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Metabolism and Antioxidant Response in Chinese Mitten Crab Eriocheir sinensis During Air Exposure and Subsequent Reimmersion

Abstract: Chinese mitten crab, Eriocheir sinensis , often suffers from severe air exposure stress during transportation and culture; high mortality occurs due to desiccation. In this study, the effects of air exposure stress (0, 2, 4, 8, and 16 h) and reimmersion (2, 6, 12 h) on respiratory metabolism and antioxidant responses in Chinese mitten crabs were studied under laboratory conditions. The results showed that air exposure and reimmersion had a significant impact on the oxygen consumption rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Thus, in hypoxic environment (like intestinal lumen), some mitochondrial bound enzymes such as SDH, mitochondrial ALT will have inhibited with simultaneous elevation of LDH. Such condition suggests a bias towards the anaerobic glycolytic pathway (41). The state that may explain a relatively higher LDH activity and lesser carbohydrate concentration and ALT activity in tissues of K. armeniaca tapeworm.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, in hypoxic environment (like intestinal lumen), some mitochondrial bound enzymes such as SDH, mitochondrial ALT will have inhibited with simultaneous elevation of LDH. Such condition suggests a bias towards the anaerobic glycolytic pathway (41). The state that may explain a relatively higher LDH activity and lesser carbohydrate concentration and ALT activity in tissues of K. armeniaca tapeworm.…”
Section: Discussionmentioning
confidence: 97%
“…Akinrotim et al (40) revealed that the elevation of LDH activity under stress conditions (like endoparasites infestation) provides the oxaloacetate that is required for the gluconeogensis pathway to meet the additional supply of glucose for the production of energy under reduced phase of oxidative metabolism. Bao et al (41) clarified that Sub lethal concentration of copper chloride resulted in significant elevation of LDH activity in muscle and hepatopancreas tissues of the crab Sesarma quadratum. They concluded that the increase in LDH activity may reflect an increased dependence on anaerobic carbohydrate metabolism by the muscle, gills and hepatopancreatic tissues upon exposer to such a toxicant (copper chloride).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDH is also a vital metabolism-regulating enzyme of anaerobic respiration and can catalyze pyruvate to lactic acid ( Schurr and Payne, 2007 ). Previous studies have shown that the activities of LDH, HK, and PK can be altered by air exposure or hypoxia stress ( Bao et al, 2019 ; Mattioli et al, 2019 ; Ding et al, 2020 ). In the present study, we found that the activities of HK, PK, and LDH increased first and then decreased during air exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of evidence indicate that severe air exposure will cause several adverse effects on aquatic animals, such as oxidative stress injury, cell apoptosis, destruction of the histological structure, disruption of energy homeostasis, poor muscle quality, reduced growth, and even death ( Arlinghaus and Hallermann, 2007 ; Gu et al, 2017 ; Lu et al, 2021 ; Harianto et al, 2022 ). To cope with desiccation and hypoxia stress of air exposure, aquatic animals can mobilize multiple adaptive physiological and molecular mechanisms, including changing respiratory metabolic strategies, enhancing immune function, increasing antioxidant defense, and altering gene expression ( Romero et al, 2007 ; Bao et al, 2019 ). At present, there are many studies on the response of various aquatic animals, including shellfish, to air exposure.…”
Section: Introductionmentioning
confidence: 99%